The Roles of Pesantren and Madrasah in Modern Society - Abdul Mujib; Yuyun Yunita; Syabbul Bachri (STAI Ma'had Aly Al-Hikam Malang, 2021)
Pesantren (Islamic boarding schools) have an independent structured learning model. The learning process is carried out informally with the sorogan and bandongan methods, which take place every day. Pesantren and Madrasah (Islamic school) are religious educational institutions managed by organizations or independently to strengthen Islam in society. There are two main strategic roles of Pesantren and Madrasah; to produce a cadre of scholars who study religion and educate students to know science, be skilled, and care about social issues. In modern developments, the demands of the role of Pesantren and Madrasah are increasingly complex. Socio-economic problems that occur in society, such as disintegration, poverty, and moral decline, are increasingly open and rampant in society and can be minimized by the presence of Pesantren and Madrasah. Therefore, Pesantren and Madrasah are expected not only to be able to solve problems related to religious beliefs but also to be involved in solving social problems.